The Role of Traditional Leaders in Hindu Marriage Traditions in Mayasari Village, South Pamona Subdistrict, Poso Regency - Armawati, Niluh Eka; Iskandar, Iskandar; Nuraedah, Nuraedah; Rore, Idrus (FKIP - Universitas Riau, 2026)
Indonesia is a country with a diverse array of ethnic groups, cultures, and religions, including Hinduism, which encompasses a wide range of traditions and religious practices. In the lives of Hindu communities, the role of traditional leaders is crucial as spiritual guides who lead the performance of religious rituals and ceremonies. This study aims to identify the requirements for becoming a traditional leader, the regulations that must be followed, and the role of traditional leaders in the implementation and preservation of Hindu marriage traditions in Mayasari Village, South Pamona Subdistrict, Poso Regency. This study employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The research informants consisted of traditional leaders, serati, and community members involved in the wedding ceremonies. The results of the study indicate that traditional leaders are selected based on good conduct, physical and spiritual health, as well as the ability to maintain personal purity and remain neutral. Traditional leaders are also required to adhere to rules regarding personal purity and moral ethics. During the marriage ceremony, traditional leaders lead the series of rituals, determine the auspicious date, oversee the preparation of offerings, and guide the community to ensure the rituals align with religious and traditional teachings. Additionally, traditional leaders play a role in preserving traditions through community education and the enforcement of customary laws. Thus, traditional leaders play a strategic role in preserving the continuity of Hindu marriage traditions in Mayasari Village.